2020
DOI: 10.1038/s41598-020-65467-2
|View full text |Cite
|
Sign up to set email alerts
|

Chloroplast development at low temperature requires the pseudouridine synthase gene TCD3 in rice

Abstract: Low temperature affects a broad spectrum of cellular components in plants, such as chloroplasts, as well as plant metabolism. on the other hand, pseudouridine (Ψ) synthases are required for the most abundant post-transcriptional modification of RNA in Escherichia coli. However, the role of rice Ψ synthases in regulating chloroplast development at low temperature remains elusive. in this study, we identified the rice thermo-sensitive chlorophyll-deficient (tcd3) mutant, which displays an albino phenotype before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…In any case, temperature appears to be an important factor when it comes to pseudouridylation within chloroplasts. Consistent with this, a mutant of the chloroplast Ψ synthase TCD3 in rice displayed thermo-sensitive changes in leaf color under cold stress and was not viable at 20 • C, but showed normal growth at 32 • C, indicating an important role of Ψ at low temperature [118]. The thermo-sensitivity of the tcd3 mutant is reflected by the differential expression pattern of plastid and presumably as a feedback effect also of cytoplasmic transcripts for chlorophyll biosynthesis, photosynthesis, plastid gene expression, and chloroplast development at 20 • C and a complete restoration to WT levels at 32 • C. In accordance with this, TCD3 is upregulated in the cold, indicating an important response at lower temperatures [118].…”
Section: Pseudouridylationsupporting
confidence: 60%
“…In any case, temperature appears to be an important factor when it comes to pseudouridylation within chloroplasts. Consistent with this, a mutant of the chloroplast Ψ synthase TCD3 in rice displayed thermo-sensitive changes in leaf color under cold stress and was not viable at 20 • C, but showed normal growth at 32 • C, indicating an important role of Ψ at low temperature [118]. The thermo-sensitivity of the tcd3 mutant is reflected by the differential expression pattern of plastid and presumably as a feedback effect also of cytoplasmic transcripts for chlorophyll biosynthesis, photosynthesis, plastid gene expression, and chloroplast development at 20 • C and a complete restoration to WT levels at 32 • C. In accordance with this, TCD3 is upregulated in the cold, indicating an important response at lower temperatures [118].…”
Section: Pseudouridylationsupporting
confidence: 60%
“…S1b,c). LOC_Os03g05806 encodes a pseudouridine synthase family protein (The Rice Genome Annotation Project; http://rice.plantbiology.msu.edu); therefore, we renamed it rice PSEUDOURIDINE SYNTHASE ( OsPUS1 ) and renamed the lts mutant as ospus1‐1 ; this gene was also previously reported as Thermo‐sensitive Chlorophyll‐Deficient TCD3 (Lin et al ., 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Except for FON1 [32] or the functional genes in the number of cloned flower organs, no other genes were evaluated. Previous studies reported important genes or gene families, such as those encoding pseudouridine synthase family protein [33], C3HC4 [34], hypothetical protein [18], protein phosphatase 2C [35], and the bZIP family transcription factor (TF) [36][37][38], related to CT in rice or other crops. Although similar genes or proteins were included in the list of 13 candidate genes, the 10 genes obtained from Gene Ontology (GO) analysis were not annotated with the phrase "response to cold".…”
Section: Putative Candidate Genes For Qcts6mentioning
confidence: 99%